2012
DOI: 10.1007/s10964-012-9843-y
|View full text |Cite
|
Sign up to set email alerts
|

Examining Associations Between Race, Urbanicity, and Patterns of Bullying Involvement

Abstract: Research on the role of race and urbanicity in bullying involvement has been limited. The present study examined bullying involvement subgroups that relate to race, urbanicity, and the perceived reason for the bullying. Self-report data were collected from 10,254 middle school youth (49.8 % female; 62.4 % Caucasian, 19.0 % African American, and 5.6 % Hispanic) and latent class analyses were used to identify three subtypes of bullying involvement: low involvement (50 %), victim (31.3 %), and bully-victim (18.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
86
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 55 publications
4
86
4
1
Order By: Relevance
“…Hispanic and black adolescents were found to be more likely to be physical bullies than their white, black and Asian peers (Nansel, et al, 2001;Wang, Iannotti, & Luk, 2012;Wang et al, 2009). Although black youth were significantly less bullied than any of their peers, they do experience racial bullying like Asian and Hispanic youth, an area often overlooked in cyber-bullying research (Arat, 2015;Fisher et al, 2015;Goldweber, Waasdorp, & Bradshaw, 2013;Nansel et al, 2001;Stone & Carlisle, 2015;Williams & Peguero, 2013). When looking at cooccurrence of traditional, non-physical bullying and cyberbullying, there were no differences among Hispanic, black, and white teens.…”
Section: Bullying and Youth Of Colormentioning
confidence: 99%
“…Hispanic and black adolescents were found to be more likely to be physical bullies than their white, black and Asian peers (Nansel, et al, 2001;Wang, Iannotti, & Luk, 2012;Wang et al, 2009). Although black youth were significantly less bullied than any of their peers, they do experience racial bullying like Asian and Hispanic youth, an area often overlooked in cyber-bullying research (Arat, 2015;Fisher et al, 2015;Goldweber, Waasdorp, & Bradshaw, 2013;Nansel et al, 2001;Stone & Carlisle, 2015;Williams & Peguero, 2013). When looking at cooccurrence of traditional, non-physical bullying and cyberbullying, there were no differences among Hispanic, black, and white teens.…”
Section: Bullying and Youth Of Colormentioning
confidence: 99%
“…African American youth have received more attention in recent studies simply because they have the greatest number of health disparities as well as higher rates of engaging in risky behaviors compared to other ethnic and age groups (Schuster et al., ). African American teenagers are also more likely to grow up in low‐income urban communities with higher rates of violence (Bradshaw, Waasdorp, Goldweber, & Johnson, ; Goldweber, Waasdorp, & Bradshaw, ). These adolescents experienced more discrimination than White and Latino adolescents and had greater exposure to violent behaviors, especially at a younger age (Schuster et al., ).…”
mentioning
confidence: 99%
“…A growing body of literature suggests that bullying behavior is more prevalent among adolescents from racial and ethnic minorities (Goldweber et al., ; Schuster et al., ; Wang, Iannotti, & Nansel, ). Bullying is defined as any aggressive behavior that is intentional, occurs repeatedly, and involves an imbalance of power or strength (Olweus, ).…”
mentioning
confidence: 99%
“…It is reported that school-aged young adults who migrate to the US are high-level cyber bullying victims. Over 10,245 urban youth in the US, African Americans have been shown to be more cyber bullying victims [12]. It is also reported that, in American secondary school students, whites experience "racial bullying" three times more than the African Americans, whereas the African Americans are twice as "racially based bullying victims" compared to whites [13].…”
Section: Literature Review 1 Risk Groupsmentioning
confidence: 99%